Genetic studies in the Pakistani population reveal novel associations with ventricular septal defects (VSDs) - Sumbal Sarwar; Shabana; Khadija Sajjad; Shahida Hasnain (BMC, 2023)
Abstract Background With prevalence up to 4%, Ventricular Septal Defect (VSD) is one of the leading causes of neonatal deaths. VSD is a common complex genetic disorder that has been associated with many genetic determinants. Variants from genes for the transcription factors including T-Box TBX5 and NFATc1 (nuclear factor of activated T cells, cytoplasmic 1), Vascular endothelial growth factor (VEGF), ISLET1 (encoded by the ISL1 gene) and enzyme MTHFR, a methylene tetrahydrofolate reductase were selected. Genetic risk score (GRS) is a widely accepted approach used to convert the genetic data into prediction and assessment tool for disease susceptibility. Methods A total of 200 participants were recruited for the current study, 100 VSD patients and 100 controls. Genotyping of the ISL1: rs1017, NFATc1: rs7240256, VEGF: rs36208048, TBX5: rs11067075, and MTHFR: rs1801133 variants was performed using tetra primer ARMS PCR and PCR-RFLP. For the statistical analysis, the software SPSS version 23 was used. Genotypic frequencies of cases and controls were calculated using chi-square (χ²) whereas allelic frequencies were calculated by using the SNPStats tool. The association of GRS quartiles with VSD was examined using binary logistic regression. Adjusted p-value 0.01 was used as significance threshold for all analyses. Results The ISL1 (OD: 0.242, CI: 0.158-0.37, p-value: 2.15 × 10− 4 :), NFATc1 (OD: 2.53, CI: 1.64-3.89, p-value: 2.11 × 10− 5), TBX5 (OD: 2.24, CI: 1.47-3.41, p-value:1.6 × 10− 4) and MTHFR (OD: 10.46, CI: 5.68-19.26, p-value: 2.09 × 10− 9:) variants were found to be in association with VSD. In contrast, the VEGF (OD: 0.952, CI: 0.56-1.62, p-value: 0.8921) variant did not show significance association with the VSD. For cases, the mean GRS score was 3.78 ± 1.285 while in controls it was 2.95 ± 1.290 (p-value: 0.479, CI: 0.474-1.190). Comparison of GRS between cases and control showed that mean GRS of cases was 1.90 ± 0.480 while in controls it was 1.68 ± 0.490 (p-value: 0.001, CI: 0.086-0.354). Higher quartiles were more prevalent in cases whereas lower quartiles were more prevalent in controls. Conclusion GRS of these five loci was strongly associated with VSD. Moreover, genetic risk score can provide better information for the association between variants and disease as compared to a single SNP. We also illustrated that the cumulative power of GRS is greater over the single SNP effect. This is a pilot scale study with a relatively small sample size whose findings should be replicated in a larger sample size for the unique local Pakistani population.